Is there any influence of the ambulatory status of children with myelomeningocele on their clinical and renal outcomes? [Meningomiyeloselli Hastalarin Yürüyebilme Durumunun Böbrek Hastaliǧi ile Ilişkili Klinik ve Radyolojik Bulgulara Etkisi Var mi?] - ALPAY, HARİKA; TARCAN, TUFAN (My University, 2012)
OBJECTIVE: The aim of this study is to evaluate the infl uence of the ambulatory status of children with MMC on renal functions, clinical and radiological fi ndings. MATERIAL and METHODS: The records of 83 children with MMC between 2005-2010 were reviewed retrospectively. The ambulatory status of the patients was classifi ed as independent walkers (walks without assistive appliances), assisted walkers (requires walking aid), and non-ambulatory (wheelchair bound) and the patient characteristics were evaluated according to the ambulatory status. RESULTS: The mean age was 7.1±0.61 years and median follow-up was 58 (32-97) months. Thirtyseven patients (44.6%) had been operated in the first three days of life. The patients with earlier initiation of follow-up earlier had less hydronephrosis and trabeculated bladder. Sixty-one children (73.5%) were non-ambulatory, 14 (16.9%) were assisted walkers and eight (9.6%) were independent walkers. GFR was less than 80 ml/minute/1.73m 2in six patients. There were no relation between ambulatory status and patients' renal functions, radiological and clinical fi ndings. CONCLUSION: Ambulatory status does not infl uence renal functions, clinical and radiological fi ndings of children with MMC. Beginning follow-up earlier may lead to fewer complications such as hydronephrosis and deformed and trabeculated bladder. Besides, patients operated in the first three days of life were more compliant with regular follow-ups.
Keywords: Ambulatory status; Meningomyelocele; Renal function